The role of Sargassum macroalgal wrack in reducing coastal erosion. (15th December 2018) - Innocenti, Rachel A.; Feagin, Rusty A.; Huff, Thomas P.
Abstract: Sea level rise and increased frequency of high-energy storms are contributing to the retreat of coastlines, impacting both natural features and coastal communities. "Soft solutions", or natural alternatives to engineered structures, have gained popularity in beach erosion mitigation; however, wrack as a method of erosion prevention remains an understudied option. The objective of our study was to test if a globally-distributed macroalgae, Sargassum spp., could act as a natural solution to moderate coastal erosion. We used a flume and increasing volumes of sargassum to consider three erosional processes at specific locations of the cross-shore profile: wave formation offshore, scouring velocity in the swash zone, and erosion on embryonic dunes. As the quantity of sargassum increased, the measureable attributes of these processes were reduced in a strongly significant manner, with large amounts of sargassum linked to 12% wave attenuation, 46% scouring velocity reduction, and 103% dune erosion reduction. Even with the lightest covering of sargassum tested, embryonic dune erosion was reduced 6% when compared to the control. These results indicate sargassum, and likely many other types of wrack, are a viable resource to help mitigate daily beach erosion.